HOTEL SERVICE TECHNOLOGIES OF TOURIST GROUPS - Horb, K. M.; Korneyev, M. V.; Pavlov, V.V. (Systems and Technologies, 2025)
The article is devoted to the analysis of approaches, generalization of experience and systematization of technologies of hotel service of tourist groups at different stages of the guest cycle, in different formats of tourist trips in different means of accommodation of tourists, including mobile ones (tourist trains, cruise ships, buses and airplanes with sleeping places, etc.), with the aim of further standardization and improvement of the group service process in tourism and hospitality. Technological processes of service of tourist groups in hotels have a number of significant differences from the provision of hotel services to individual guests. At the stage of booking hotel services for a group of tourists, it is important for the customer to provide the hotel with a list of tourists with their passport data, to agree on the distribution of tourists by rooms of different categories, with the priority of compact mutual arrangement of rooms where the tourists of the group will live, as well as the issue of group transfer to the hotel upon arrival and return transfer upon departure, to take care of parking at the hotel of the group vehicle. At the accommodation stage, it is important to promptly settle the group members in the hotel rooms through the coordinated actions of the hotel administrator on duty and the tour group guide. During the group’s stay at the hotel, it is important to ensure the compatibility of the purpose of the group’s stay with the purpose of the rest of the guests. At the last stage of final settlements, eviction and departure of the group from the hotel, it is important to ensure the efficiency of mutually agreed actions regarding checking rooms, handing over keys, packing personal belongings and loading them into a vehicle, etc. When providing group hotel services to tourists at each stage of the guest cycle, the key task is to avoid queues and minimize the time for any waiting by the majority of the group of the rest of the tourists. All of the above provisions for hotel services for tourist groups are valid for both stationary facilities and accommodation establishments and for mobile ones, namely for those tourist vehicles where it is intended to provide tourists with sleeping places for overnight stays. In the future, it is appropriate to pay attention to a more detailed justification of the concept of a group guest cycle of an accommodation facility, the essence of which will be the consist- ency and continuity of providing group hotel service.